The Strategy of Dairy Goat Business Development - Choirunisa, Zulfiana; Imam Santoso, Siswanto; Ekowati, Titik (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 15 No 3 (2021): Vol.15, No.3, 2021, 2021)
The Kuncen Farm Livestock Farmers Group (KTT) was one of the livestock farmers group in Semarang City where the dairy goat commodity has problems in sales and has an impact on the income. The problems included the demand for goat's milk was influenced by people's purchasing power, people's habits of consuming cow's milk, productivity was not optimal, competition factors between goat's milk businesses, marketing, and lack of capital to develop the business. The aims of the research were to analyze the farmers’ income, analyze internal factors (strengths and weaknesses) and analyze external factors (opportunities and threats) at the Kuncen Farm KTT. The research method was the census method. The respondents came from 21 members of the Kuncen Farm KTT, members of the Department of Agriculture and the Department of Food Security. Data analysis method by income calculations and analysis of three strategic formulations included the matrix of Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), Internal-External (IE), SWOT and Quantitative Strategic Planning (QSP). The research results were the average farmers’ income was 883,864 Rupiah/month and the calculation of the R/C ratio was 1.58>1 which means that the business was economically profitable. Analysis of internal and external factors in the development of dairy goat business had the biggest strength, which was the processing of dairy products, the biggest weakness was no group role in marketing, the biggest opportunity was the high purchasing power of the people and the biggest threat was the product less attractive. The strategy priority was to inform the community about the benefits of goat's milk in group.